2014
DOI: 10.1002/adv.21493
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Analysis of Hydroxypropylmethyl Cellulose and Pectin‐Based Controlled Release Matrix Tablets Loaded with Loxoprofen Sodium

Abstract: ABSTRACT:The basic purpose of the current study was to formulate controlled release matrix tablets loaded with loxoprofen sodium using pectin and hydroxypropylmethyl cellulose (HPMC). The effect of these polymers on the release pattern of drug from the formulated matrix system was evaluated. Different concentrations of these polymers alone as well as polymeric blends were used in tablets formulation using wet granulation technique. The differential scanning calorimetric technique was used to detect the chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Therefore, by controlling the concentration of the polymer, thickness can be controlled, and hence the release of the drug. Findings of the current studies were in agreement with the stated claim, as the formulations with lower amounts of TAX released greater amounts of TZN HCl, and vice versa (figure 11) [24,43].…”
Section: In Vitro Drug Release Studiessupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, by controlling the concentration of the polymer, thickness can be controlled, and hence the release of the drug. Findings of the current studies were in agreement with the stated claim, as the formulations with lower amounts of TAX released greater amounts of TZN HCl, and vice versa (figure 11) [24,43].…”
Section: In Vitro Drug Release Studiessupporting
confidence: 87%
“…A fixed funnel and cone method was used to measure the angle of repose [24]. A glass petri dish was placed on a flat surface, and a glass funnel fixed over it with the help of a tripod stand, in such a way that the distance between its tip and a paper surface was 20 mm.…”
Section: Angle Of Reposementioning
confidence: 99%
“…Positive values of constant, which was the mean of the variable in the polynomial Equation , described that response was optimistic and results were signifying the impact of both independent variables, on the drug release (Figures e and ). HPMC E5 showed negative impact, which means that increase in the concentration of polymer would lower down the release of the drug . PEG 400 had shown positive effect and positive values predicted that increase in PEG 400 concentration would enhance the dissolution of MLX and hence the amount of the drug release.…”
Section: Resultsmentioning
confidence: 99%
“…However, cumulative percentage drug of initial 5 min was taken for analysis. [58] PEG 400 had shown positive effect and positive values predicted that increase in PEG 400 concentration would enhance the dissolution of MLX and hence the amount of the drug release. (a) Showing amount of drug released from F1 to F3, (b and c) showing amount of the drug released from F4 to F6 and from F7 to F9, respectively, while (d) describing permeated amount of drug through goat buccal mucosa from F2, F4, and F7 | 1831 ZAZAN ZANnd ZANNIF as the p value was less than .05 (.0460).…”
Section: Percent Drug Releasementioning
confidence: 99%
“…Due to the short elimination half-life of approximately 65 min [12], the commercial tablet of LXP has to be administrated three times a day to maintain the therapeutic concentration in plasma, which might cause high risks of gastrointestinal (GI) lesions and systemic side effects [13,14]. Several studies have been reported on the preparation of LXP sustained release dosage forms [15,16,17]. However, due to its high solubility, most of the preparations, especially for the matrix-based formulations, showed a burst release (drug release >30%) during the first 2 h [18], which could cause unexpected GI mucosal injury for patients.…”
Section: Introductionmentioning
confidence: 99%